MODERN CHALLENGES IN LINGUISTICS: EXPLORING THE INTERSECTION OF LANGUAGE, PSYCHOLOGY, TECHNOLOGY AND SOCIETY - Atajanova , Nazokat Mansur qizi (Educational Research in Universal Sciences, 2023)
This article discusses the most prominent modern problems that linguistics is currently facing. The evolving nature of language, together with integration with other fields such as psychology and technology, has created challenges, including language variation and change, multilingualism, technology, language and thought, AI and machine learning, dialectology, social media impact, speech and language pathology, translanguaging, and corpus linguistics. These challenges require a multi-disciplinary approach to be effectively addressed and are opportunities for innovation and development in linguistics.